A philosophy of the possible : modalities in thought and culture - Epstein, Mikhail, (Value Inquiry Book Series, 2019)
In this book, Mikhail Epstein offers a systematic theory of modalities (the actual, possible, and necessary), as applied to the discourse of philosophy in its post-Kantian and especially post-Derridean perspectives. He relies on his own experience of living in the USSR and the US, dominated respectively by imperative and possibilist modalities. Possibilism assumes that a thing or event acquires meaning only in the context of its multiple possibilities, inviting counterfactual and conditional modes of description. The author focuses on the creative potentials of possibilistic thinking and its heuristic value. The book demonstrates the range of modal approaches to society, culture, ethics, and language, and outlines potentiology as a new philosophical discipline interacting with ontology and epistemology.